Disability, Bias, and AI - Whittaker, Meredith; Alper, Meryl; Bennett, Cynthia L.; Hendren, Sara; Kaziunas, Liz; Mills, Mara; Morris, Meredith Ringel; Rankin, Joy; Rogers, Emily; Salas, Marcel; West, Sarah Myers (AI Now Institute, 2019)
On March 28, 2019, the AI Now Institute at New York University (NYU), the NYU Center for Disability Studies, and Microsoft convened disability scholars, AI developers, and computer science and human-computer interaction researchers to discuss the intersection of disability, bias, and AI, and to identify areas where more research and intervention are needed. This report captures and expands on some of the themes that emerged during discussion and debate. In particular, it identifies key questions that a focus on disability raises for the project of understanding the social implications of AI, and for ensuring that AI technologies don’t reproduce and extend histories of marginalization.